THE VALIDITY OF TEXTBOOK BASED ON READING, QUESTIONING AND ANSWERING (RQA) FOR LEADING STUDENTS IN ASSESSMENT COURSE AT CHEMISTRY DEPARTMENT UNESA - Nasrudin, Harun; Azizah, Utiya; Muchlis, Muchlis (Universitas Negeri Surabaya, 2018)
This study aims to determine the validity of textbook based Reading, Questioning and Answering (RQA) in process assessment and learning outcomes course at chemistry department Unesa. The research method uses research and development (R & D).The results showed that the textbook based RQA was feasible in term of construct validity with very valid category, content validity with very valid category, language and readability with valid category, and in accordance with the RQA strategy with a valid category.From this research, it can be concluded that the texbook suitable for use in process assessment and learning outcomes course.